2021
DOI: 10.3390/s21030704
|View full text |Cite
|
Sign up to set email alerts
|

Night-Time Monitoring System (eNightLog) for Elderly Wandering Behavior

Abstract: Wandering is a common behavioral disorder in the community-dwelling elderly. More than two-thirds of caregivers believe that wandering would cause falls. While physical restraint is a common measure to address wandering, it could trigger challenging behavior in approximately 80% of the elderly with dementia. This study aims to develop a virtual restraint using a night monitoring system (eNightLog) to provide a safe environment for the elderly and mitigate the caregiver burden. The eNightLog system consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The long-term goal of this research is to develop a sleep surveillance system that can track participants’ sleeping postures and behaviors, and it represents a milestone in establishing baseline parameters to classify postures and remedy the pragmatic problems of blankets in a controlled setting. We achieved another milestone in monitoring the behavior of getting out of bed in a previous paper [ 20 ]. The next step is to consider real-world sleeping conditions and evaluate the proportion of each posture across the time axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term goal of this research is to develop a sleep surveillance system that can track participants’ sleeping postures and behaviors, and it represents a milestone in establishing baseline parameters to classify postures and remedy the pragmatic problems of blankets in a controlled setting. We achieved another milestone in monitoring the behavior of getting out of bed in a previous paper [ 20 ]. The next step is to consider real-world sleeping conditions and evaluate the proportion of each posture across the time axis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is also essential to monitor sleeping posture for individuals at risk of falling out of bed, particularly elderly people with dementia or delirium, or those at the end of life [ 19 ]. While pressure mats and infrared fences have been routinely exploited for this purpose, some researchers developed an integrated depth camera and impulse radar system to monitor wandering behavior and alarm caregivers when elderly people get out of bed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This field study is built on the work of our previous research which evaluated the eNightLog system in a controlled setting only [ 56 ]. This field study tested 17 sets of the systems in one hostel over 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…In view of this, a night-time monitoring system, the eNightLog system, has been developed to monitor elderly night-time activities and prevent wandering, using non-contact sensors that can overcome some limitations of pressure mats and infrared fences. The performance of the eNightLog system was proven to be superior to the integrated pressure mat and infrared fence system in a laboratory test simulating nursing home settings in our previous work [ 56 ]. However, the system has not been evaluated with elderly people with dementia living in a hostel setting.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies 8 , 16 , 20 have identified the risk factors of PR use among older adults in LTC facilities and developed various interventions, including behavioral and psychiatric symptoms management, 21 quality improvement project, 22 alternatives of PR, 23 staff education programs, 23 multicomponent interventions. 24 , 25 Therein, nursing staff education on PR is the most commonly used strategy because nursing staff plays a vital role in the process of PR use in LTC.…”
Section: Introductionmentioning
confidence: 99%